Evaluation on the Squeezing and Design of Support system in Headrace Tunnel of Middle Modi Hydroelectic Project - Banjade, Basanta (Kathford Journal of Engineering and Management, 2023)
Tunneling through a weak rock possess a great challenge. These challenges depends upon type of rock, excavation method, stress and deformation behavior of the rock etc. Squeezing is one of the major problem which is likely to occur during excavation of tunnel through weak rock. A reliable prediction of the extent of squeezing is essential so that a strategy can be established regarding stabilizing measures and for optimizing the support well in advance. In this paper, Middle Modi Hydroelectric Project located in the Kaski District has been taken as the case study. In this project, huge squeezing problem occurred at about chainage 1+140m At this section deformation has been recorded well over 65cm Hence, this paper basically deals with squeezing analysis using different approaches. Rock types along the headrace tunnel alignment are sheared phyllite and fractured quartzite. Mostly, intercalation of phyllite and quartzite has been found in the squeezed section Rockmass quality found in the squeezed section is extremely poor to exceptionally poor. Four main methods have been used to evaluate the squeezing phenomenon viz empirical methods such as Singh (1992) and Goel (2000), semi-empirical such as Hoek and Marinos (2000), analytical method such as (Convergence Confinement Method, 2000) and mumerical program Phase2. The main factors that control the squeezing phenomenon are the rock mass parameters and rock stresses. The uniaxial unconfined compressive strength of intact rock has been back calculated from measured deformations using phase2 program and found to be in the range of 10 to 15Mpa in the squeezed section Deformation was calculated using CCM and Compared with phase2 result. Due to excessive deformation temporary supports were provided at several locations, steel ribs are buckled and shotcrete lining is also cracked. All these have to be removed before application of final lining Finally two different approaches have been studied using phase program to address the existing problems in squeezed section of headrace tunnel ie. design of support system considering either circular shape with final lining (shotcrete and steel rib) or reshaping existing D-shaped tunnel into horseshoe shaped and providing final concrete lining.